Strange Animals/Seduced Human Beings: The Monsters in Rima de Vallbona’s Stories - Chen Sham, Jorge (2014)
The reaction of horror and fear, of attraction and vertigo that monsters produce, starts in Rima de Vallbona with the familiar element of the pet. Thus, the Costa Rican-American writer reinterprets the fantastic before what is described as a perversion/fascination that awakens our deepest fears with the monster that hides behind a dog or a cat. The pets in our homes turn into a fatal attraction and a servant-master relationship in “My Alter Animus (Parable)” and into a dizzying destabilizing experience in “My Friend Irene’s Nahual’.